Innovación y competitividad en el sector artesanal del distrito de San Juan Bautista 2024 - Rojas Panduro, Rosa Angélica (2025)
The study aimed to determine the relationship between innovation and competitiveness in the artisan sector of the San Juan Bautista district, 2024. To this end, a basic research study was conducted with a non-experimental, cross-sectional, correlational design. The study population consisted of 113 artisans, selected for their significant contribution to the local culture and economy. The results indicated that 47% of the artisans considered innovation to be average. This result is due to the fact that, in the last three years, some businesses have occasionally introduced new products aimed at the international market. However, the products launched during this period were almost always innovative for both the business and the market. Regarding competitiveness, 49% of the artisans rated it as average. This perception is related to the fact that they sometimes make efforts to standardize their products according to market demands, and only occasionally implement quality controls following the technical specifications of the craft items. In conclusion, the results showed a direct, moderate to strong relationship (r = 0.761) between innovation and competitiveness in the artisanal sector of the San Juan Bautista district, 2024. Furthermore, the bilateral significance value obtained (p = 0.000) statistically confirms this correlation.